ANALISIS LABA DAN DIVIDEN TERHADAP HARGA SAHAM PADA PERUSAHAAN YANG TERGABUNG DALAM INDEKS LQ-45 DI BURSA EFEK INDONESIA - Kadek Wulandari Laksmi (Jurnal Ilmiah Akuntansi & Bisnis, 2017)
Investors before investing in a company would pay attention to certain things that are beneficial to them. Things that concern is profits and of course with the dividend announcement. Earnings provide information on how the company's performance. While the dividend is a distribution of company profits to shareholders. From that information, the investor can make the decision to invest or not. Investor's decision to invest in a company will certainly affect the stock price of the company. The purpose of this study was to 1) test and analyze the effect of earnings to share price, 2) test and analyze the effect of dividend announcements on stock prices. Outcomes to be achieved are: 1) The Company can maximize its performance so that it can generate high profit, 2) With high profit the company can divide its profit to shareholders in the form of dividends, 3) In addition to the company's survival is assured, high profits will increase stock prices because investors will be attracted to invest in the company. This research was conducted at a company incorporated in the LQ-45 index in the Indonesia Stock Exchange from 2011-2014. Source data used are secondary data and data types are quantitative data in the form of income statements, announcements of dividends and stock prices in 2011-2014. The method used in this study are parametric statistics. Dioalah of the collected data using SPSS. The results are then analyzed and the results desired. Based on the research while the obtained results that 1) profit significant no effect on stock prices, 2) the dividend announcement no significant effect on stock prices. In this case investors and prospective investors are not focused on profits generated by the company and they preferred the retained earnings and used for business development compared with distributed as dividends. Keywords: Earnings, Dividend and Stock Price